The keys to the house - Dräger, Jascha,Müller, Nora,Pforr, Klaus (German Socio-Economic Panel (SOEP), DIW Berlin, 2024)
This study investigates how actual and anticipated intergenerational wealth transfers (i.e., inter-vivo gifts and inheritances) contribute to social stratification in the transition to homeownership. Utilizing discrete-time survival analysis on data from the German Socio-Economic Panel Study (N=13,018), we find that individuals whose parents were manual workers or service workers are less likely to become homeowners. Receiving inheritances or inter-vivo gifts substantially increases the probability of becoming a homeowner, with the effect being most pronounced in the transfer year and diminishing rapidly after that. Anticipated future transfers also increase homeownership probability before transfer receipt. Anticipated and received together transfers explain up to 56% of the variation in homeownership transition rates by parental socio-economic status but the importance of transfers for the transition to homeownership varies strongly across class contrasts. Ignoring expected transfers leads to a significant underestimation of the importance of transfers on the effect of parental SES on homeownership.
10419/305201
Keywords: Graue Literatur; Social stratification; homeownership; inheritance; intergenerational transfers